2017
DOI: 10.1097/mlr.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Veterans

Abstract: Our evidence maps provide a "lay of the land" and identify important gaps in knowledge about health disparities experienced by different Veteran populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 3 publications
0
27
2
Order By: Relevance
“…This report also indicated that overall quality of care varied by geographic region in which a person resided, with some people having lower quality of care based on where they lived [20]. In the US Department of Veterans Affairs (VA), VA patients with mental health conditions and those of lower socioeconomic status had significantly poorer health outcomes than those who did not have mental health conditions or higher socioeconomic status [21]. As a final example of health outcome disparities, in 2013, cardiovascular disease, HIV, and diabetes rates were significantly higher among people of color than white individuals [22].…”
Section: Introductionmentioning
confidence: 99%
“…This report also indicated that overall quality of care varied by geographic region in which a person resided, with some people having lower quality of care based on where they lived [20]. In the US Department of Veterans Affairs (VA), VA patients with mental health conditions and those of lower socioeconomic status had significantly poorer health outcomes than those who did not have mental health conditions or higher socioeconomic status [21]. As a final example of health outcome disparities, in 2013, cardiovascular disease, HIV, and diabetes rates were significantly higher among people of color than white individuals [22].…”
Section: Introductionmentioning
confidence: 99%
“…While research with veterans has identified significant disparities in arthritis pain management and choice of interventions among VHA patients (24,25), less is understood about psychosocial mechanisms of disparities in OA-related health outcomes. Clarifying the links among cumulative disadvantage, perceived discrimination, and health among veterans with OA is particularly important, given the increasing diversity and aging nature of the veteran population, their high risk for declines in health, and ongoing efforts by the VHA to eliminate health disparities (3,26).…”
Section: Introductionmentioning
confidence: 99%
“… 7 8 It is likely that nearly 3 million other veterans have pre-diabetes. These high rates compared with the general population may be due to the increased proportions of overweight (37%) and obesity (41%) among veterans, 9 their older age, lower socioeconomic status 10 and possible exposure to herbicides such as Agent Orange. 11…”
Section: Introductionmentioning
confidence: 99%